Mapping Research Trends On Artificial Intelligence And Green Marketing Strategies In Shaping Sustainable Consumer Behavior: A Systematic Literature Review - Muhammad Umam Mubarok; Budi Santoso; Eko Budi Satoto (Journal of Studies in Academic, Humanities, Research, and Innovation, 2025)
The convergence of Artificial Intelligence (AI) and green marketing has become a pivotal topic in shaping sustainable consumer behavior amid global digital transformation and environmental challenges. However, previous studies remain fragmented, focusing separately on technological efficiency or environmental ethics without providing an integrated understanding of their intersection. This study aims to map and analyze global research trends on the integration of AI and green marketing strategies in influencing sustainable consumer behavior. Using a Systematic Literature Review (SLR) approach guided by the PRISMA protocol, this research systematically identified, screened, and synthesized peer-reviewed articles published between 2015 and 2025 across leading academic databases such as Scopus and Google Scholar. The analysis reveals an evolutionary trajectory of research from conceptual frameworks and ethical foundations toward data-driven personalization, transparency, and algorithmic accountability. Findings show that AI is increasingly recognized not only as a technological enabler but also as a strategic and ethical catalyst capable of enhancing consumer awareness, credibility, and engagement in sustainability-oriented marketing ecosystems. This synthesis highlights a paradigm shift where intelligent systems contribute to behavioral transformation by aligning digital innovation with ecological responsibility. The study concludes that integrating AI and green marketing provides a new framework for ethical, data-informed, and sustainability-driven marketing practices that support both environmental goals and consumer well-being.